2016
DOI: 10.1002/fuce.201500038
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Carbon Deposition from CH4 onto the Ni/YSZ Anode of SOFCs

Abstract: A challenge in the operation of solid oxide fuel cells (SOFCs) with hydrocarbon fuels is the carbon deposition on the nickel/yttria‐stabilized zirconia (Ni/YSZ) anode. The Grabke‐type kinetic model has been proposed for the carbon formation based upon the assumption of elementary steps, which consist of a rate‐limiting dissociative chemisorption step and a stepwise dehydrogenation of the chemisorbed methyl group. This work experimentally studied the carbon formation on a SOFC Ni/YSZ anode exposed to CH4+H2 gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…When increasing the energy cutoff to 500 eV, the oxygen vacancy formation energies for a YSZ system changed by less than 0.03 eV regardless of the applied field strength . To model the triple phase boundary between a Ni cluster and a YSZ support, a Ni/YSZ slab with a unit cell dimension of 7.25 Å × 12.56 Å (Figure ) was used, which is similar to the Ni/YSZ model proposed by Shishkin and Ziegler. ,, In the calculations, a Monkhorst–Pack mesh with a (4 × 2 × 1) k-points grid was chosen for the Brillouin zone integration. To avoid field emission as well as the interaction between each periodic supercell in the perpendicular direction, a 12 Å vacuum was used in our model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When increasing the energy cutoff to 500 eV, the oxygen vacancy formation energies for a YSZ system changed by less than 0.03 eV regardless of the applied field strength . To model the triple phase boundary between a Ni cluster and a YSZ support, a Ni/YSZ slab with a unit cell dimension of 7.25 Å × 12.56 Å (Figure ) was used, which is similar to the Ni/YSZ model proposed by Shishkin and Ziegler. ,, In the calculations, a Monkhorst–Pack mesh with a (4 × 2 × 1) k-points grid was chosen for the Brillouin zone integration. To avoid field emission as well as the interaction between each periodic supercell in the perpendicular direction, a 12 Å vacuum was used in our model.…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical cells containing Ni with a yttria-stabilized zirconia support (Ni/YSZ) have become an attractive and high efficiency energy conversion technology, which produces less harmful greenhouse emissions as compared to the traditional fuel combustion process. , For example, direct-methane solid oxide fuel cells (SOFCs) at high temperatures can convert chemical energy (CH 4 ) directly to electricity. Methane can also be activated in a solid electrolyte (i.e., Ni/YSZ) single-chamber cell, which applies electricity to dramatically alter the production yield or selectivity. , In such cases, the nonfaradaic electrochemical modification of catalytic activity (NEMCA) caused by the applied electric potential is observed and contributes to changes in the catalyst work function, as well as the interaction between the catalytic surface and the fuel . However, one of the major issues facing the use of a Ni/YSZ cermet for hydrocarbon fuel activation is its catalytic degradation by sulfur poisoning and coking. Since such a degradation usually occurs at the oxygen vacancies in the triple phase boundary (TPB) region of the Ni/YSZ cermet, it is essential to understand the kinetics involved in the formation of oxygen vacancies over the TPB area of Ni/YSZ via H 2 oxidation in a direct-methane electrochemical cell environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used the thermodynamic data for graphite when calculating the equilibrium constant for the Boudouard reaction , , . However, there is a significant difference between the thermodynamic data for graphite and filamentous carbon , , .…”
Section: Introductionmentioning
confidence: 99%
“…The elementary step of methane decomposition is shown in Table.6 [65]. P.Fan and co-workers [66] further studied the carbon formation in a methane and hydrogen mixed atmosphere and calculated all the kinetic model by assuming each step was the rate-determining step. After running the experiments, they found that only the methane chemisorption step was verified to be the rate-limiting step.…”
Section: Kinetics Of Carbon Deposition For Methane Steam Reformingmentioning
confidence: 99%